ANALISIS STRATEGI TELEMARKETING PADA BANK BTN KC JAKARTA PLUIT - Mohamad Rizki (2022)
Rapid technological advances, resulting in rapid communication and encouraging integration in the banking world. Business activities are experiencing a new phase as a result of technological advances, one of which is activities in marketing products. This has encouraged various companies, including the financial sector, one of which is the banking industry using the telemarketing method. The purpose of this research is to find out the telemarketing strategy of Bank BTN KC Jakarta Pluit. The research method used is a qualitative case study approach. Data obtained through interviews, direct observation and documentation. Data analysis was performed using Microsoft Excel. The results of the analysis using the effectiveness criteria of telemarketing can be categorized as very effective.